Hidden Cardiovascular Anatomy in “Saint John the Baptist” by Leonardo da Vinci - Keshelava, Grigol (AORTA, 2022)
Leonardo da Vinci conducted many anatomical studies during his life. Today, almost the complete set of these anatomical drawings and comments is owned by the British Crown and resides in the Royal Library at Windsor Castle, United Kingdom.Through the program Paint X, we moved two details on the painting “Saint John the Baptist.” The moving details are circled along the faint contour by Leonardo da Vinci himself. We obtained heart and aortic arch imaging.
Keywords: cardiovascular anatomy; Saint John the Baptist; Leonardo da Vinci